Cross-Channel Geographers: a century of activity. - Hugh Clout (Cybergeo, 2005)
Despite their spatial proximity, British and French geographers have undertaken relatively little research about each other’s countries. This article provides a reasoned –but personal - account of what has been accomplished in cross-Channel geography during the 20th century, paying attention to the authors involved, their academic milieux and their orientations within the discipline. French geographers have been especially attracted to topics in physical geography in the British Isles, whereas British geographers have emphasized research into the human and historical geography of France. Despite a certain reticence on both sides, enormous opportunities for cross-Channel research remain for the future.